Evaluating emergency‐release blood transfusion of newborn infants at the Intermountain Healthcare hospitals. Issue 10 (3rd September 2019) - Bahr, Timothy M.; DuPont, Tara L.; Christensen, Thomas R.; Rees, Terry; O'Brien, Elizabeth A.; Ilstrup, Sarah J.; Christensen, Robert D.
Abstract : BACKGROUND: An emergency‐release blood transfusion (ERBT) protocol (uncrossmatched type O‐negative red blood cells, AB plasma, AB platelets) is critical for neonatology practice. However, few reports of emergency transfusions are available. We conducted an ERBT quality improvement project as a basis for progress. STUDY DESIGN AND METHODS: For each ERBT in the past 8 years, we logged indications, products, locations and timing of the transfusions, and outcomes. RESULTS: One hundred forty‐nine ERBTs were administered; 42% involved a single blood product, and 58% involved two or more. The incidence was 6.25 ERBT per 10, 000 live births, with a higher rate (9.52 ERBT/10, 000) in hospitals with a Level 3 neonatal intensive care unit (NICU) (p < 0.001). Seventy percent of ERBTs were administered in a NICU and 30% in a delivery room, operating room, or emergency department. Indications were abruption/previa (32.2%), congenital anemia (i.e., fetomaternal hemorrhage; 15.4%), umbilical cord accident (i.e., velamentous insertion; 15.0%), and bleeding/coagulopathy (12.8%). Fifty‐eight percent of those with hemorrhage before birth did not have a hemoglobin value reported on the umbilical cord gas; thus, anemia was not recognized initially. None of the 149 ERBTs were administered using a blood warmer. The mortality rate of recipients was 35%. CONCLUSION: Based on our findings, we recommend including a hemoglobin value with every cord blood gas after emergency delivery to rapidly identify fetal anemia. We also discuss two potential improvements for future testing: 1) the use of a warming device for massive transfusion of neonates and 2) the use of low‐titer group O cold‐stored whole blood for massive hemorrhage in neonates.